2020
DOI: 10.1038/s41598-020-63265-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ABCB1 gene polymorphism and its expression on non-small-cell lung cancer development, progression and therapy – preliminary report

Abstract: the ABCB1 gene belongs to Atp binding cassette (ABc) transporter genes that has been previously implicated in cancer progression and drug response. this study aimed to evaluate the association between the SNP 3435 and the expression of the ABCB1 gene in lung cancer patients in the polish population in comparison to clinicopathological parameters and treatment. 150 RNA and 47 DNA samples were isolated from 49 lung cancer cases including both tissue samples and blood taken from the same patients at three time po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…Wnt/β-catenin pathway is an important regulator of many cellular processes, including cell proliferation, development, tumorigenesis, and homeostasis 53 , 54 . This analysis correlates with several prior studies, which have associated the Wnt/β-catenin pathway activation to chemoresistance through the upregulation of the ABCB1 gene in several cancer types 55 , 56 , including LC 57 , 58 . Our RNA-seq data present differentially increased Wnt genes, including WNT5A, WNT7B, and a 120-fold increase of the ABCB1 gene.…”
Section: Discussionsupporting
confidence: 89%
“…Wnt/β-catenin pathway is an important regulator of many cellular processes, including cell proliferation, development, tumorigenesis, and homeostasis 53 , 54 . This analysis correlates with several prior studies, which have associated the Wnt/β-catenin pathway activation to chemoresistance through the upregulation of the ABCB1 gene in several cancer types 55 , 56 , including LC 57 , 58 . Our RNA-seq data present differentially increased Wnt genes, including WNT5A, WNT7B, and a 120-fold increase of the ABCB1 gene.…”
Section: Discussionsupporting
confidence: 89%
“…The ABCB1 gene is highly polymorphic in nature, and it has been reported that multiple polymorphisms of this gene may be associated with P-gp, which is linked with various processes such as apoptosis, cellular proliferation, differentiation, and immune system mechanisms. 38,39 Genetic polymorphisms are correlated with the alterations in the quantity or activity of different membrane transporters or proteins, leading to a change in the physiological activities, which further results in disease progression. 40,41 As a result of the characteristic polymorphisms, the ABCB1 gene has been widely investigated, and approximately 66 SNPs of this gene have been identified, among which 22 SNPs are synonymous and others are non-synonymous.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ABCB1 mRNA level grew over time in blood samples taken from lung cancer patients, suggesting an important contribution of ABCB1 in lung cancer MDR. 37 In the ABCC1 and ABCG2 genes, the alteration in the expression and the effectiveness of the corresponding gene and its product were located in the single nucleotide polymorphisms (SNPs). Thus, they might elevate the risk and impact the response of the cancer cells to the treatment and increase the capability of other types of cancer.…”
Section: Discussionmentioning
confidence: 99%